2015
DOI: 10.5966/sctm.2014-0267
|View full text |Cite
|
Sign up to set email alerts
|

Human Umbilical Cord Mesenchymal Stem Cell Exosomes Enhance Angiogenesis Through the Wnt4/β-Catenin Pathway

Abstract: Human umbilical cord mesenchymal stem cells (hucMSCs) and their exosomes have been considered as potential therapeutic tools for tissue regeneration; however, the underlying mechanisms are still not well understood. In this study, we isolated and characterized the exosomes from hucMSCs (hucMSC-Ex) and demonstrated that hucMSC-Ex promoted the proliferation, migration, and tube formation of endothelial cells in a dose-dependent manner. Furthermore, we demonstrated that hucMSC-Ex promoted wound healing and angiog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
340
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 392 publications
(354 citation statements)
references
References 53 publications
12
340
1
1
Order By: Relevance
“…Bone marrow-derived MSC exosomes increase the number of mature NeuN positive cells in lesioned striatum (Doeppner et al, 2015a) and prevent post-stroke immune suppression that is a common sequela of clinical stroke. Cord blood-derived MSC exosomes are pro-angiogenic (Zhang et al, 2015) while EPC exosomes contain miR-126 and miR-296 which activates the PI3K/Akt signaling pathway in endothelial cells (Deregibus et al, 2007). The NSC cell-line, CTX0E03, produces exosomes with a myriad of miRNAs, although the most abundant was miR-1246 (Stevanato et al, 2016).…”
Section: Putative Therapies For Enhancing Brain Self-repair and Strokmentioning
confidence: 99%
“…Bone marrow-derived MSC exosomes increase the number of mature NeuN positive cells in lesioned striatum (Doeppner et al, 2015a) and prevent post-stroke immune suppression that is a common sequela of clinical stroke. Cord blood-derived MSC exosomes are pro-angiogenic (Zhang et al, 2015) while EPC exosomes contain miR-126 and miR-296 which activates the PI3K/Akt signaling pathway in endothelial cells (Deregibus et al, 2007). The NSC cell-line, CTX0E03, produces exosomes with a myriad of miRNAs, although the most abundant was miR-1246 (Stevanato et al, 2016).…”
Section: Putative Therapies For Enhancing Brain Self-repair and Strokmentioning
confidence: 99%
“…In contrast, WNT4 has been shown to decrease cell migration of rat thyroid cells FRTL-5 suggesting that it can exert different actions depending on the cellular context (De Menna et al 2013). It was recently shown that WNT4 secretion by human umbilical cord mesenchymal stem cells stimulates their migration, and is activating angiogenesis in vivo in a rat skin burn model (Zhang et al 2015). Interestingly, exosomal release of WNT4 is responsible for mesenchymal stem cell migration (Zhang et al 2015), and similar exosome release of WNT5a induces human melanoma cancer cell migration and invasion (Ekström et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…It was recently shown that WNT4 secretion by human umbilical cord mesenchymal stem cells stimulates their migration, and is activating angiogenesis in vivo in a rat skin burn model (Zhang et al 2015). Interestingly, exosomal release of WNT4 is responsible for mesenchymal stem cell migration (Zhang et al 2015), and similar exosome release of WNT5a induces human melanoma cancer cell migration and invasion (Ekström et al 2014). Whether a similar mechanism is involved for WNT4-induced migration of normal mammary epithelial cells needs to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Human umbilical cord MSC-derived exosomes (hucMSC-Exos) through the Wnt4 pathway are also involved in skin wound healing. HucMSC-Exos facilitate the function of endothelial cells; various studies have demonstrated that the hucMSC-Exo-mediated Wnt4 pathway induced β-catenin activation in endothelial cells and enhanced vascular regeneration (57,67). Furthermore, research has suggested that exosomes from the serum may accelerate wound healing in mice, predominantly due to the impact on collagen synthesis (68).…”
Section: Exosomes and Skin Wound Healingmentioning
confidence: 99%